Clinical Practice Guideline Development Manual, Third Edition: A Quality‐Driven Approach for Translating Evidence into Action. (14th December 2012) - Rosenfeld, Richard M.; Shiffman, Richard N.; Robertson, Peter
Abstract : Background: Guidelines translate best evidence into best practice. A well‐crafted guideline promotes quality by reducing health care variations, improving diagnostic accuracy, promoting effective therapy, and discouraging ineffective—or potentially harmful—interventions. Despite a plethora of published guidelines, methodology is often poorly defined and varies greatly within and among organizations. Purpose: The third edition of this manual describes the principles and practices used successfully by the American Academy of Otolaryngology—Head and Neck Surgery Foundation to produce quality‐driven, evidence‐based guidelines using efficient and transparent methodology for actionable recommendations with multidisciplinary applicability. The development process emphasizes a logical sequence of key action statements supported by amplifying text, action statement profiles, and recommendation grades linking action to evidence. New material in this edition includes standards for trustworthy guidelines, updated classification of evidence levels, increased patient and public involvement, assessing confidence in the evidence, documenting differences of opinion, expanded discussion of conflict of interest, and use of computerized decision support for crafting actionable recommendations. Conclusion: As clinical practice guidelines become more prominent as a key metric of quality health care, organizations must develop efficient production strategies that balance rigor and pragmatism. Equally important, clinicians must become savvy in understanding what guidelines are—and are not—and how they are best used to improve care. The information in this manual should help clinicians and organizations achieve these goals.